2019
DOI: 10.1111/ijfs.14128
|View full text |Cite
|
Sign up to set email alerts
|

Food uses of pineapple waste and by‐products: a review

Abstract: Waste from fruits and vegetable processing industry is produced in large quantities worldwide and it contains high levels of lignocellulose, fibre, sugar, bioactive and functional compounds. Their utilisation has become one of the main important and challengeable aspects due to the generation of large quantities of by-products including peels, seeds, leaves and unused flesh in different steps of processing chain. Many researches have validated the waste utilisation as novel, low-cost, economical and natural so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 45 publications
1
42
0
3
Order By: Relevance
“…Very quickly, the optimization design of bromelain isolation was studied by the application of electrolyte precipitation, using a natural polysaccharide in pineapple by-products crude juices. In very specific and studied conditions, the efficient precipitation of bromelain was enabled, obtaining high yields of extraction and high enzyme activity recovery [14]. Through the described methodology, it was possible to separate and concentrate the most important enzyme from pineapple-Stem Bromelain.…”
Section: Liquid Phase Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Very quickly, the optimization design of bromelain isolation was studied by the application of electrolyte precipitation, using a natural polysaccharide in pineapple by-products crude juices. In very specific and studied conditions, the efficient precipitation of bromelain was enabled, obtaining high yields of extraction and high enzyme activity recovery [14]. Through the described methodology, it was possible to separate and concentrate the most important enzyme from pineapple-Stem Bromelain.…”
Section: Liquid Phase Separationmentioning
confidence: 99%
“…Some authors have described the application of pineapple waste as a substrate not only of bromelain but also for ethanol, sugars, vitamins, and growth factors [13]. Moreover, pineapple by-products have been studied as a low-cost substrate for the production of various organic acids, especially citric, lactic, and ferulic acids, using fermentation technology due to the commercial value of these products in the market since they are widely used in food, pharmaceutical, and beverage industries for acidification and enhancement of flavor [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Estes subprodutos têm o potencial para serem convertidos em produtos comestíveis e considerados como matériaprima, de baixo custo e acessível. Muitas das vezes, eles são ricos em carboidratos, fibras, minerais e tem alta atividade antioxidante, sendo boa fonte de nutrientes e componentes funcionais (Kowalska et al, 2017;Rico et al, 2020;Roda & Lambri, 2019).…”
Section: Introductionunclassified
“…Research has validated that pineapple waste contain beneficial compound as good as the fruit itself. Roda and Lambri [11] had listed the good nutrients in pineapple waste comprising insoluble fibres, simple sugars, vitamins, good enzymes such as bromelain. This review paper also concluded that pineapple waste has a great potential to be explored as a valuable substrate if appropriate processes and technologies are applied accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in waste management and exploring the use of agricultural waste as antinutrient are most needed, as an effort to overcome both environmental pollution and seasonal food farming losses [2,4,11]. The aim of our work was to increase the current understanding on nutritional composition and level of antinutrient factors in high value agricultural waste in Malaysia.…”
Section: Introductionmentioning
confidence: 99%